1982
DOI: 10.3171/jns.1982.56.3.0448
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic myelopathy secondary to ossified ligamentum flavum

Abstract: The authors report a case of ossification of the ligamentum flavum at T-10 and T-11 associated with compressive myelopathy. Metrizamide myelography with computerized tomography allowed precise preoperative diagnosis and anatomic localization of the lesion. The patient had satisfactory and prompt improvement after surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Before the early 1990s, when MRI was not commonly used for neurological diagnosis, CT was considered the best diagnostic tool to detect thoracic OLF. 23,26,30,36 OLF can be confirmed to mainly present in the foraminal region on CT, which not only provide an accurate assessment of the contour of the ossification but also show the ossification of dura mater and the size of the spinal canal. Pascal-Moussellard et al 28 reported sagittal reconstructions of CT that are helpful for distinguishing OLF from calcification of the ligamenta flava, which is the only differential diagnosis of OLF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the early 1990s, when MRI was not commonly used for neurological diagnosis, CT was considered the best diagnostic tool to detect thoracic OLF. 23,26,30,36 OLF can be confirmed to mainly present in the foraminal region on CT, which not only provide an accurate assessment of the contour of the ossification but also show the ossification of dura mater and the size of the spinal canal. Pascal-Moussellard et al 28 reported sagittal reconstructions of CT that are helpful for distinguishing OLF from calcification of the ligamenta flava, which is the only differential diagnosis of OLF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when the ligamentum flavum is replaced by a mature bone, its osseous morphology should be V-shaped or a part of V shape on CT images. 12 Although thoracic OLF has been reported in several Asian countries, such as Japan, [11][12][13][14] China 3,4,[15][16][17][18][19] and South Korea, [20][21][22] and also in Caucasian and Caribbean ethnic groups, [23][24][25][26][27][28] extensive studies on thoracic OLF including a large number of patients have not yet been reported in the literature. This is partly due to the relatively low mean prevalence of thoracic OLF, which was reported as 3.8% in China and as 6.2% for Japanese men and 4.8% for Japanese women.…”
Section: Introductionmentioning
confidence: 99%
“…8 The segments most frequently involved in thoracic stenosis were lower thoracic (T9 ± T12), in which there is great mobility and vulnerability to¯exion, extension, and rotation. 9,10 Both the frequency and severity of ossi®cation of ligamentum¯avum increase as the thoracolumbar junction is approached; this is because the lower thoracic spine undergoes local mechanical stress from tensile force due to frequent motion. 11 Cases in which there was signi®cant stenosis in other segments are summarized in Table 3.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…A less recognised cause is the ossification of the ligamenta flava (OLF), a condition that is rarely reported in the Western literature. Although thoracic OLF usually occurs in the lower thoracic spine, [1][2][3][4][5][6][7][8][9][10] it has been reported to occur at higher thoracic levels resulting in proximal myelopathy. 11,12 This is particularly important because, regardless of the level and severity of the disease, OLF is easily treatable by decompressive laminectomy if the diagnosis is made early.…”
Section: Introductionmentioning
confidence: 99%